Control the properties of high-strength aluminum alloy systems Al-Zn-Mg-Cu to prevent premature failure - Abolikhina O. V.; Chernega Svitlana M. (Металознавство та обробка металів, 2019)
High-strength aluminum alloys of V93T1, V93hpT3, 1933T3, made of forged or stamped semi-finished products, along with duralumin, are the main material for the design elements of airframes. The work on improving the service characteristics of the alloy B93 has been under way for more than six decades since its inception due to the optimization of the composition, the introduction of new alloyed microadditives and the use of step-by-step heat treatment This allowed the creation of an improved alloy of 1933, which replaced the AK6 and B93 alloys. However, as shown by the experience of using the alloy in 1933, in the conditions of long-acting alternating loads and aggressive media, it is still sensitive to stress concentrators and is prone to fatigue and corrosion fatigue. The paper shows the history of the development of high-strength alloys of the Al-Zn-Mg-Cu system used in aircraft of different generations.